Penerapan Digital Marketing pada PT Citra Marindo - Kristina Thai; Listia Nurjanah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This community service activity aims to provide solutions to the challenges faced by PT Citra Marindo in implementing digital marketing. PT Citra Marindo, a company engaged in providing products and services for the maritime industry, encounters obstacles in fully leveraging the potential of digital marketing. This activity focuses on assisting the company in improving and enhancing their digital marketing strategies. A more comprehensive digital marketing implementation was applied through various social media platforms such as Instagram, WhatsApp Business, and e-commerce platforms like Tokopedia. Additionally, business branding development included designing more attractive logos, professional product photos, and packaging that aligns with market preferences. Quality control systems were introduced to ensure high product quality, while effective promotional strategies were implemented to increase brand visibility and awareness among consumers. All steps were tailored to real-world conditions, including cost calculations for marketing elements to ensure they do not burden product prices and can be sustained. It is hoped that this activity will have a positive impact on increasing PT Citra Marindo business profits and serve as a useful reference for other businesses facing similar issues